Reflections on the capital market and economy - Uwaleke, Uchenna Joseph (Abuja, Nigeria Aridos Press, 2018)
A compilation of the author's well-researched articles on contemporary issues around the capital market and the Nigerian economy published in three Nigeria's national newspapers.
oif 19/09/2018
Loans
Keywords: Capital market; Economy; Nigeria